Menelaah Hubungan Antara Iklim Kerja dan Kinerja Karyawan: Peran Mediasi Spiritualitas di Tempat Kerja pada PT. Gramasurya Yogyakarta - Baedhowi, Abdul Latif; Abdul Choliq Hidayat; Siswanto, Agus (Forum Kerjasama Pendidikan Tinggi, 2024)
This study examines the impact of work climate on employee performance, with a particular focus on the mediating role of workplace spirituality. Using a sample of 70 permanent employees from PT. Gramasurya Yogyakarta, this research aims to provide a comprehensive understanding of the factors influencing employee performance. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM PLS). The results confirm all proposed hypotheses, indicating that both work climate and workplace spirituality positively affect employee performance. Furthermore, workplace spirituality significantly mediates the relationship between work climate and employee performance intentions. These findings underscore the importance of enhancing work climate and workplace spirituality to improve employee performance. By emphasizing the significance of workplace spirituality, companies can increase employee engagement. Employees who perceive their work environment as supportive of their spirituality tend to be more productive.